Toward The Best Model In Recruitment Process And Employee Competence In Outsourcing Industries - Soelton, Mochamad (Jurnal Ekonomi, 2018)
This study aims to examine and analyze the effect of the recruitment process, selection process and employee competence on outsourced employee performance( in outsourcing Industries). Data was collected through questionnaires distributed and executed on 70 employees of outsourcing of commercial division, data analysis in this research using non- probability sampling technique and using saturation sampling where its data processing using Statistical Package for Social Science (SPSS) version 23 program. The results of the analysis show that the Recruitment Process, Selection process and Competence have the positive and significant impact on Employee Performance.